Elongated odontoid process in late Holocene skeletal remains from B6 archaeological site, Mendoza, Argentina - Suby, Jorge Alejandro (2018)
The odontoid process of the axis can be affected by congenital or acquired pathologies. While abnormalities such as os odontoideum, agenesis, and fractures are reported in archaeological remains, the abnormality of an elongated length of the odontoid process has not been described in the paleopathological literature. The aim of this paper is to evaluate two individuals with elongated odontoid processes from a skeletal assemblage from the B6 archaeological site (Mendoza, Argentina), and to discuss the possible etiologies of the condition, with particular attention given to the relation to trauma and Crowned Dens Syndrome (CDS), a condition characterized by the ossification of ligaments of the odontoid process of the second cervical vertebra.